Limitations of reliance on specific IgE for epidemiologic surveillance of food allergy - Keet, Corinne A.; Wood, Robert A.; Matsui, Elizabeth C. (Journal of allergy and clinical immunology, 2012)
[...]in the extensive literature review conducted for development of the National Institute of Allergy and Infectious Diseases Guidelines for the Diagnosis and Management of Food Allergy, the authors could only conclude that food allergy affects more than 1% to 2% but <10% of the population.1 Allergen-specific IgE offers a potential surrogate. According to the cutoffs used by others,3 for each food we divided subjects into groups defined by food-specific IgE: "unlikely food allergy" (food-specific IgE of 0.35-2 kU/L), "probable food allergy" (food-specific IgE between 2 and 7 kU/L for egg, 15 kU/L for milk, 14 kU/L for peanut, and 5 kU/L for shrimp), and "likely food allergy" (food-specific IgE above those levels).